2016
DOI: 10.1586/17474124.2016.1121810
|View full text |Cite
|
Sign up to set email alerts
|

Proposed therapies in primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC), previously known as primary biliary cirrhosis, is a model autoimmune disease with chronic cholestasis characterized by the hallmark of anti-mitochondrial antibodies and treated with ursodeoxycholic acid (UDCA). However, approximately 20-40% of patients incompletely respond to UDCA and have an increased risk of disease progression. Although there have been significant advances in the immunobiology of PBC, these have yet to be translated into newer therapeutic modalities. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 132 publications
2
7
0
Order By: Relevance
“…Interestingly, treatment with CVC alone did not reduce cholestatic liver injury in either rodent models, including an absence of an effect on liver necrosis, fibrosis and even bile duct proliferation. This observation is consistent with reports from clinical trials in PBC patients where there was a lack of efficacy when immunosuppressive drugs were tested . However, at the molecular level, CVC treatment alone reduced hepatic expression of pro‐inflammatory cytokine Ccl2, Ccl5, Tnf‐α and IL‐6 in these cholestatic animals (Figures & ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, treatment with CVC alone did not reduce cholestatic liver injury in either rodent models, including an absence of an effect on liver necrosis, fibrosis and even bile duct proliferation. This observation is consistent with reports from clinical trials in PBC patients where there was a lack of efficacy when immunosuppressive drugs were tested . However, at the molecular level, CVC treatment alone reduced hepatic expression of pro‐inflammatory cytokine Ccl2, Ccl5, Tnf‐α and IL‐6 in these cholestatic animals (Figures & ).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, obeticholic acid has been approved by the FDA for treating PBC patients with inadequate responses or intolerance to UDCA, but pruritus and hyperlipidaemia are significant side effects . Therefore, there is a need for developing additional therapeutic approaches for PBC and other cholestatic disorders …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…non-Hodgkin' s lymphoma), it has also been found to be therapeutic in various autoimmune diseases. 57 An open label study of rituximab usage in PBC included 14 patients on UDCA (without biochemical remission) who were administered two infusions (1000 mg) 2 weeks apart and followed for 72 weeks. 56 Effective B-cell depletion was achieved in 93% (13/14) subjects but response was not sustained with rebound increase in circulating plasma B-cells after 12 weeks.…”
Section: Biologicsmentioning
confidence: 99%
“…IL-12 and IL-23 are the main antigens-two cytokines paramount to Th1/Th17 signaling in PBC. 57 A phase II multicenter study evaluating the efficacy and safety of ustekinumab in 20 PBC subjects revealed no significant improvement in ALP at 12 or 28 weeks with ustekinumab therapy (NCT0138997). Other clinical trials ongoing evaluating various immunomodulatory agents in PBC refractory to UDCA include: CTLA-4 Ig (abatacept, NCT02078882) and CD40-anatagonist monoclonal antibody (FFP104, NCT02193360).…”
Section: Biologicsmentioning
confidence: 99%